(untitled) (Journal Of Educational and Psychological Researches, 2025)
The current research aims to construct an enrichment program according to the strength of cognitive control for gifted female students in the first intermediate grade and to identify the impact of the enrichment program on the perceived self-efficacy of gifted female students in the first intermediate year. To achieve the research objectives, an experimental method was adopted. The research population consisted of first-grade middle school female students in gifted schools affiliated with the directorates general (first, second, and third) of education in Al-Rusafa of education in Baghdad Governorate for the academic year 2023-2024. The experiment was applied to a sample of 54 female students chosen randomly from six schools. An enrichment program was constructed based on the cognitive control power, which included three chapters from the first-grade middle school mathematics book (fifth, sixth, and seventh). A self-efficacy scale of 39 items was developed at three levels: choosing activities, effort exerted, and persistence in performing tasks to measure perceived self-efficacy. The experimental group was taught using the traditional method in addition to the enrichment program, while the control group was taught according to the traditional teaching method. The results showed that the experimental group outperformed the control group in terms of the perceived self-efficacy scale.